Adsorption and removal studies of heavy metal Pb(II) on their Water Solution on adsorbent surface of Vinyl Alcohol/Chitosan-Graphene Oxide. Issue 1 (June 2021) - Jasim, Layth S.; Irhayyim, Sajjad H.
Abstract: Chitosan/polyvinyl alcohol/graphene oxide (CH-g-PVA/GO) hydrogel was prepared by using iron chloride as a cross-linking agent. This hydrogel was used to remove lead ions as it was found to have a suitable surface area for adsorption time was 120 mint. The adsorption is proven using FESEM and FTIR analysis, TEM analysis, and knowledge of AFM surface roughness.. Also, TGA shows that the hydrogel is stable at high temperatures. The study of the hydrogel's kinetic parameter was performed by using the lead ion applied to the adsorption of the pseudo-second-order because (R 2 ) approximates the correct model.